STUDENTS’ EXPERIENCES ON ENGLISH LEARNING CLASS DURING ONLINE LEARNING: NARRATIVE INQUIRY - Ika Lestari; Maman Suryaman; Nina Puspitaloka (PROJECT (Professional Journal of English Education), 2022)
This narrative study aims to explore the students' motivational experience of two English education students in Indonesia during the COVID-19 pandemic. The research was conducted by using a qualitative approach and narrative inquiry method. The research participants were two students second and fourth semester at the university of Singaperbangsa Karawang. To collect the data, researchers used were interviews. Drawing on semi-structured interview data, we found the prevalence of online courses affected students' emotions and motivation. Both participants experienced emotions and motivation facing the online courses. The study stresses the students’ experience, emotional experiences during online class, and factors that motivated learning. Keywords:  Online learning, English Learning, Students’ Experiences